Genetic basis for developmental toxicity due to statin intake using embryonic stem cell differentiation model. (October 2015) - Jyoti, S; Tandon, S
The in utero environment is a key factor controlling the fate of the growing embryo. The deleterious effects of statins during the fetal development are still not very well understood. Data from animal studies and retrospective studies performed in pregnant women give conflicting reports. In this study, using in vitro differentiation model of embryonic stem cells, which mimic the differentiation process of the embryo, we have systematically exposed the cells to lipophilic statins, simvastatin, and atorvastatin at various doses and at critical times during differentiation. The analysis of key genes controlling the differentiation into ecto-, meso- and endodermal lineages was assessed by quantitative polymerase chain reaction. Our results show that genes of the mesodermal lineage were most sensitive to statins, leading to changes in the transcript levels of brachyury, Flk-1, Nkx2.5, and α/β-myosin heavy chain. In addition, changes to endodermal marker α-fetoprotein, along with ectodermal Nes and Neurofilament 200 kDa, imply that during early differentiation exposure to these drugs leads to altered signaling, which could translate to the congenital abnormalities seen in the heart and limbs.